2009
DOI: 10.1097/scs.0b013e31819922fb
|View full text |Cite
|
Sign up to set email alerts
|

Use of Resorbable Implants for Mandibular Fixation

Abstract: Titanium plating is recognized as the criterion standard for the treatment of mandibular fractures and osteotomies. Use of resorbable implants is well documented in the literature for a range of craniofacial fractures. However, no clear review exists of the use of resorbable implants on the mandible. In this systematic review, we searched MEDLINE/PubMed and the Cochrane Database for studies of resorbable mandibular fixation. Two independent reviewers analyzed the search results using specific inclusion/exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 36 publications
0
36
0
5
Order By: Relevance
“…Aliphatic polyesters such as PLLA/PDLA, PLLLA/ PGA, PCL and others have demonstrated excellent safety profiles in multiple in vitro, animal and clinical studies and have received approval for clinical applications mainly in the oral and maxillofacial region [19][20][21]. Polymer/calcium phosphate composites such as mPCL-TCP or PDLLA-TCP-PCL confer favourable mechanical and biochemical properties, including strength via the ceramic phase and toughness and plasticity via the polymer phase.…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic polyesters such as PLLA/PDLA, PLLLA/ PGA, PCL and others have demonstrated excellent safety profiles in multiple in vitro, animal and clinical studies and have received approval for clinical applications mainly in the oral and maxillofacial region [19][20][21]. Polymer/calcium phosphate composites such as mPCL-TCP or PDLLA-TCP-PCL confer favourable mechanical and biochemical properties, including strength via the ceramic phase and toughness and plasticity via the polymer phase.…”
Section: Discussionmentioning
confidence: 99%
“…The average degradation time is approximately 12 --18 months. The mechanical strength of PDLLA could last for 3 --6 months in vivo, which is beneficial for maintaining the early fixation and non-weight-bearing area for bone repair [16]. Histological results have shown that the surface modified three-dimensional (3D) chitosan/PDLLA scaffolds possess significantly higher bone formation potential and better biocompatibility than pure porous PDLLA scaffold in a rabbit radialis defect model in vivo [17].…”
Section: Introductionmentioning
confidence: 85%
“…Further developments in improving the strength, rate of degradation and biocompatibility of these materials has resulted in the use of biodegradable osteosynthesis in a wide range of craniomaxillofacial procedures such as pediatric craniofacial surgery [18] , mandibular fractures [19] , fractures of the frontal sinus [20] , maxillary osteotomies and sagittal split mandibular osteotomies [21] .…”
Section: Resorbable Osteosynthesis Materialsmentioning
confidence: 99%